Observations of open‐ocean deep convection in the northwestern Mediterranean Sea: Seasonal and interannual variability of mixing and deep water masses for the 2007‐2013 Period. Issue 11 (10th November 2016) - Houpert, L.; Durrieu de Madron, X.; Testor, P.; Bosse, A.; D'Ortenzio, F.; Bouin, M. N.; Dausse, D.; Le Goff, H.; Kunesch, S.; Labaste, M.; Coppola, L.; Mortier, L.; et al.
Abstract: We present here a unique oceanographic and meteorological data set focus on the deep convection processes. Our results are essentially based on in situ data (mooring, research vessel, glider, and profiling float) collected from a multiplatform and integrated monitoring system (MOOSE: Mediterranean Ocean Observing System on Environment), which monitored continuously the northwestern Mediterranean Sea since 2007, and in particular high‐frequency potential temperature, salinity, and current measurements from the mooring LION located within the convection region. From 2009 to 2013, the mixed layer depth reaches the seabed, at a depth of 2330m, in February. Then, the violent vertical mixing of the whole water column lasts between 9 and 12 days setting up the characteristics of the newly formed deep water. Each deep convection winter formed a new warmer and saltier "vintage" of deep water. These sudden inputs of salt and heat in the deep ocean are responsible for trends in salinity (3.3 ± 0.2 × 10 −3 /yr) and potential temperature (3.2 ± 0.5 × 10 −3 C/yr) observed from 2009 to 2013 for the 600–2300 m layer. For the first time, the overlapping of the three "phases" of deep convection can be observed, with secondary vertical mixing events (2–4 days) after the beginning of the restratification phase, and the restratification/spreading phase still active at the beginning of the following deep convection event. Key Points: Continuous monitoring of five consecutive winters of deep convection that reached the seabed, found at a depth of 2300 m Observation of the overlapping of the deep convection phases (vertical mixing/restratification; spreading/preconditioning) Formation of warmer and saltier new deep water mass "vintages" after each event of deep convection